The Influence of Corporate Social Responsibility, Company Size, Capital Structure, Profitability and Leverage on Company Value in Manufacturing Companies Listed on the Indonesia Stock Exchange in 2017-2019 - Mega Agus Thio; Ninta Katharina (Jurnal Mantik, 2021)
The purpose of this research is to determine the effect of CSR, Company Size, Capital Structure, Profitability and Leverage on Firm Value in manufacturing companies. In the implementation of this study, the population used is manufacturing companies listed on the Indonesia Stock Exchange for the period 2017 to 2019. In this study, the sampling technique used was purposive sampling. The data used is secondary data, with documentation study techniques. The method of data analysis is multiple linear regression. Based on the results of the study, it shows that CSR and Profitability have an effect on Firm Value, while Company Size, Capital Structure and Leverage have no significant effect on Firm Value.